2016
DOI: 10.1123/jab.2015-0214
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Intersession Reliability of Surface Electromyography on Muscles Actuating the Forearm During Maximum Voluntary Contractions

Abstract: The aim of this study is to determine the intra- and intersession reliability of nonnormalized surface electromyography (sEMG) on the muscles actuating the forearm during maximum voluntary isometric contractions (MVIC). A subobjective of this study is to determine the intra- and intersession reliability of forearm MVIC force or torque, which is a prerequisite to assess sEMG reliability. Eighteen healthy adults participated at 4 different times: baseline, 1-h post, 6-h post, and 24-h post. They performed 3 MVIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The ICC values for MVIC ranged from 0.622 to 0.876, which reflected good to excellent reliability (8). These findings were similar to those of Gaudet et al (16) and Smith et al (40) who reported ICC values that ranged from 0.534 to 0.960 for MVIC values during isometric forearm flexion. In addition, there were no differences between test visits for the neuromuscular parameters (EMG AMP, EMG MPF, MMG AMP, and MMG MPF) during the pretest MVICs.…”
Section: Discussionsupporting
confidence: 92%
“…The ICC values for MVIC ranged from 0.622 to 0.876, which reflected good to excellent reliability (8). These findings were similar to those of Gaudet et al (16) and Smith et al (40) who reported ICC values that ranged from 0.534 to 0.960 for MVIC values during isometric forearm flexion. In addition, there were no differences between test visits for the neuromuscular parameters (EMG AMP, EMG MPF, MMG AMP, and MMG MPF) during the pretest MVICs.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, a relatively low ICC (range: 0.57–0.80) was seen in the BB in intersession single measurement. However, the average of repeated sEMG measurement was considered to obtain high reliability rather than single measurement [ 23 ]. Kollmitzer et al evaluated the intersession reliability of measures of the knee extensor group (RF, vastus lateralis, and medialis muscles) and found that the overall reliability was good, especially for the RF muscle [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wireless BTS-FREEEMG 300 (BTS Bioengineering, Milan, Italy) was used to collect the surface electromyography (sEMG) signals of the paretic TA muscle, which were synchronously transmitted to a BTS EMG-Analyzer (BTS Bioengineering) [ 15 ]. Patients were asked to sit comfortably in a chair with knees flexed at 90 degrees, ankles in an anatomically neutral position.…”
Section: Methodsmentioning
confidence: 99%